Harvest Time and Postharvest Behavior of Six Japanese Nonastringent Persimmon Cultivars Grown under Mediterranean Conditions - Ayoub Fathi-Najafabadi; Cristina Besada; Rebeca Gil; Alejandra Salvador (HortScience, 2020)
Persimmon cultivation has significantly grown in the Mediterranean Region in recent years. The production concentrates mainly in three astringent cultivars: Kaki Tipo in Italy, Triumph in Israel, and Rojo Brillante in Spain. Therefore, the varietal range expansion is one of the current challenges for persimmon producers in this area. Moreover, the introduction of nonastringent persimmon cultivars is particularly interesting because they can be commercialized immediately after harvest without applying deastringency treatment before commercialization. This study evaluated the harvest period and the postharvest response of six Japanese nonastringent cultivars (Kanshu, Shinshu, Soshu, Suruga, Youhou, Izu). During two seasons, fruit from each cultivar were harvested at two maturity stages. Fruit quality (external color, firmness, and total soluble solids) was evaluated after harvest and after different commercial scenarios (domestic market: 7 days at 20 °C, market to European Union (EU): 5 days at 5 °C plus 5 days at 20 °C, and market to countries with cold-quarantine treatment requirements: 21 days at 0 °C plus 5 days at 20 °C). Cultivars Kanshu, Shinshu, Soshu, and Izu were identified as early cultivars, and Soshu was the earliest one, which reached commercial maturity at the beginning of September. These four cultivars showed good quality after simulating commercialization on domestic and EU markets. Cultivars Suruga and Youhou overlapped the current harvest window, but their low chilling injury sensitiveness is highlighted, so they are of special interest to be cold-stored at the end of the season to be commercialized in overseas markets.